A Pragmatic Analysis of Illocutionary Act Used in Valley of The Lanterns Movie - Ni Wayan Swarniti (Universitas Pahlawan Tuanku Tambusai, 2023)
The aim of this research was to classify and analysis illocutionary act used in Valley of The Lanterns movie. This research was done by qualitative and descriptive method. The data were utterances that indicated as illocutionary act used in Valley of The Lanterns Movie. Data was collected by observational method. The data were then classified and categorized based on the categories of illocutionary act proposed by Searle (1969). Each of data was analyzed in detail descriptively. The result of analysis was concluded that all the types of illocutionary act found in Valley of The Lanterns Movie. Directives (59,58 % or 171 data). Representatives (26,83 % or 77 data). Expressive (6,27 % or 18 data). Commissives (5,58 % or 16 data). Declarative (1,74 % or 5 data). Declarative was type of illocutionary act that found in the data source in low quantity. Directive was the most type of illocutionary act found in data source. It means the utterances in the data source mostly contain the information of asking, commanding, requesting, and warning.